VISUAL NAVIGATION IN THE INFRASTRUCTURE OF PUBLIC TRANSPORT OF KHARKOV IN CURRENT CONDITIONS FROM THE POSITION OF EUROPEAN EXPERIENCE - Holius, V. (Municipal economy of cities. Series: «Economy science», 2022)
The article examines issues related to the need to develop and features of a visual navigation system in the public transport infrastructure of the city of Kharkiv from the perspective of European projects currently being implemented in the city. Kharkiv and O.M.Beketov National University of Urban Economy in Kharkiv, in particular, are taking part in the implementation of the German-Swiss project "Integrated development of cities in Ukraine", the transport infrastructure of the city is being studied. Thus, the Kharkiv City Council signed a protocol on cooperation with the German federal company GIZ in the framework of the implementation of the project "Integrated development of cities in Ukraine II" in 2019, thereby joining the second phase of the initiative (2019–2023). The training events made it possible to improve cooperation, communication and coordination between various structural units of the city councils. In view of the results of this project, it is proposed to investigate the possibility of developing and using a visual navigation system in the public transport infrastructure of the city of Kharkiv and its features, based on European experience and taking into account harmonious integration into the overall branding of Kharkiv. The relevance of this issue is reinforced by the constant increase in the needs of citizens in public transport, which is primarily related to the growth of urban trends and the ecological vector of technology development. For Kharkiv, this issue is becoming even more urgent in modern conditions: it is planned to develop new public routes, making them more adaptable, increasing the number of electric buses, developing the city’s bicycle infrastructure. The result of the project will be an impetus in the development of transport infrastructure, transformation and adaptation in view of modern conditions and European trends. Which, in turn, indicates the need for a systematic and complex approach in the development of visual navigation and taking into account the peculiarities of territory branding. Certain components that can be implemented in the formation of a complex of graphic and design solutions in navigation for the city of Kharkiv are considered.